Forecasting Foreign Institutional Investors’ (FII) Investment Flows in India: An Autoregressive Model - Mohanasundaram, T.; Karthikeyan, P.; Shanthi, D. (Arthshastra Indian Journal of Economics & Research, 2018)
India is considered as one of the fastest emerging economies in the world and a leading nation in attracting foreign investments. The country offers huge investment opportunities to reap benefits for both domestic and foreign institutional investors (FIIs) in its equity market. India’s FII investments are characterized by positive net inflows in most of the years since its inception in 1992. Only duringÂ 1998-99 and 2008-09, FII outflows were higher than inflows. Many earlier studies have concluded that FII flows were largely influenced by the Indian stock market returns. Considering the volatile nature of FII investment flows, this study attempted to forecast FII flows in Indian stock market using an autoregressive model. Net FII investments and stock market returns data from July 2013 to December 2015 were used to estimate an autoregressive model. Net FII flows from January 2016 to June 2016 were forecasted based on the formulated estimation. The forecasted values were then compared with the actual values to verify the model’s reliability. The autoregressive model used in the study was an acceptable model as forecast errors were minimal, and it captured the investment trends correctly. Forecasting the FII investments can help in better policy formulation and are useful for making strategic decisions in the capital market.